Dreaming in adolescents during the COVID-19 health crisis: survey among a sample of European school students - Guerrero-Gomez, Ana; Nöthen-Garunja, Isabel; Schredl, Michael; Homberg, Annelore; Vulcan, Maria; Brusić, Asja; Bonizzi, Caterina; Iannaco, Cecilia (Frontiers in psychology, 2021)
According to the continuity hypothesis of dreaming and contemporary psychodynamic approaches, dreams reflect waking life. The aim of the present study was to explore the relationship between the Covid-19 pandemic and dreaming in adolescents. A cross-sectional survey was conducted in Italy, Romania and Croatia involving 2105 secondary school students (69% girls, mean age 15.6 ± 2.1 years; 31% boys, mean age 15.1 ± 2.2 years; mean age of whole sample 15.4 ± 2.1 years). No substantial differences between countries were found. 31% of the participants reported heightened dream recall, 18% noticed an increase in nightmares during the lockdown and 15% of the provided dreams (n=498) included pandemic-related content. The results indicate that subjective emotional reactions to lockdown had a significantly higher correlation to dreaming than objective distress (i.e. illness or death of a close one because of Covid-19). These findings suggest that attention to dreams should be included in preventive programs for adolescents with pandemic-related stress.
Gesehen am 30.06.2021